THE INFLUENCES OF PRODUCT, PRICE, AFTER SALES SERVICE AND ADVERTISING ON CONSUMER PURCHASE INTENTION OF MPV CAR (CASE STUDY OF SUZUKI ERTIGA) - oroh, Glevino E; Massie, James D. D.; Tumbuan, Willem J.F. Alfa (Universitas Sam Ratulangi, 2019)
Abstract: Nowadays, car has important things in order to face the high mobility. One of that is MPV car. Suzuki is one of the automotive company that popping MPV car known as Suzuki Ertiga. Many factors are influencing consumer to buy MPV car such as product, price, after sales service and advertising. This research is conduct in Manado. The objective of this research are to analyze the influences of Product, Price, After Sales Service and Advertising on Consumer Purchase Intention of MPV car (Case Study of Suzuki Ertiga), partially and simultaneously. This research is using a multiple regression model. The population of this study is a consumer of MPV car (Suzuki Ertiga) in Manado, where sample taken by 100 respondent. The conclusion of this study is generally Price and After Sales Service does not significant influences to Consumer Purchase Intention and Product and advertising have significant influences to Consumer Purchase Intention. Based on this research, The Company should pay serious attention to product and advertising in order to survive in tight business competition and can attract the consumer by offering products that meet with their needs and wants. Keyword: product, price, after sales service, advertising, consumer purchase intention, MPV car